Backlash in action? or inaction? stalled implementation of the domestic violence (prevention and protection) Act 2010 in Bangladesh - Sultan, Maheen; Mahpara, Pragyna (Institute of Development Studies, 2024)
While the formulation and enactment of the Act was an achievement for the government and the coalition that championed it (the Citizens’ Initiative Against Domestic Violence, CIDV), its implementation has been weak. In Bangladesh, dominant social norms have led to stereotyping domestic violence as a trivial, personal matter, which has led to service providers delegitimising and deprioritising the issue. Combined with all the gender biases that operate within the judiciary and other government departments, this has resulted in an unsatisfactory use of the Act for women seeking redress from violence. This paper explores to what extent this lax implementation is due to the weak capacity of implementing agencies versus deliberate/intentional inaction in the form of backlash. It also examines how women’s rights organisations have articulated feminist voices in terms of agenda and framing and used collective agency to counter the pushback.